Atopic dermatitis, systemic inflammation and subsequent dementia risk - Snieguole Vingeliene; Ayako Hiyoshi; Michael Carlberg; Miguel Garcia‐Argibay; Marleen Lentjes; Katja Fall; Laura vonKobyletzki; Scott Montgomery (Wiley, 2023)
Abstract Background Atopic dermatitis is a chronic inflammatory skin disease and inflammation has been implicated in development of other chronic diseases, but few studies have examined the relationship with dementia. Objectives This study examines associations of atopic dermatitis (AD) and systemic inflammation in adolescence measured using erythrocyte sedimentation rate (ESR), as well as AD diagnosed in adulthood, with dementia risk. Methods We used three Swedish register‐based cohorts. Cohort I (N = 795,680) comprised men, born in 1951-1968, who participated in the military conscription examinations with physician‐assessed AD and ESR; Cohort II (N = 1,757,600) included men and women, born in 1951-1968; and Cohort III (N = 3,988,783) included all individuals in Sweden, born in 1930-1968. We used Cox regression, estimating hazard ratios (HR), with the follow‐up from 50 years of age to dementia diagnosis, date of emigration, death, or 31 December 2018, whichever occurred first. Further, we used a sibling comparison design to adjust for unmeasured confounders shared among siblings. Results Cohort I: 1466 dementia events were accrued during follow‐up of 7.8 years, with a crude rate of 21.6 [95% confidence interval (CI): 20.6, 22.8] per 100,000 person‐years. Cohort II: 3549 dementia events were accrued during follow‐up of 7.4 years, with a crude rate of 23.7 (95% CI: 22.9, 24.5) per 100,000 person‐years. Cohort III: 120,303 dementia events were accrued during follow‐up of 23.7 years, with a crude rate of 180.3 (95% CI: 179.3, 181.3) per 100,000 person‐years. In multivariable analysis using Cohort I, there was no association between AD and dementia [HR 0.68 (95% CI 0.32, 1.43)], nor with moderate [HR 0.71 (95% CI: 0.46, 1.10)] or high [HR 1.23 (95% CI: 0.87, 1.75)] ESR. AD was not associated with dementia risk in Cohort II [HR 1.28 (0.97, 1.71)] or Cohort III [HR 1.01 (0.92, 1.11)]. Conclusions AD was not associated with dementia risk, neither was systemic inflammation measured by ESR in adolescence.